Climate risk profiles and agricultural vulnerability in Africa: A multi-dimensional analysis - Guo, Zhe; Yang, Ruixin (Institute of Electrical and Electronics Engineers, 2024)
Climate risk profile studies play a vital role in Africa, considering the continent’s unique vulnerability to climate change. With diverse ecosystems, economies, and social contexts, Africa faces a multitude of climate-related risks, including extreme weather events, water scarcity, agricultural disruptions. Understanding and assessing these risks through climate risk profile studies is crucial for effective adaptation and mitigation planning. Our study aimed to construct seasonal crop risk profiles utilizing a composite index methodology, analyzing historical climate data spanning the past three decades. This composite index integrates spatially explicit evaluations of heat stress, drought stress, and flood hazards. Specifically focused on agricultural risks, our study further refines these hazards concerning crops during the growing seasons. Furthermore, our analysis will assess changes and trends in the frequency and severity of these hazards over time. These investigations offer invaluable insights into the precise climate threats confronting African nations and regions, empowering policymakers and communities to make well-informed decisions regarding resource allocation, infrastructure development, and socioeconomic planning.